Ferroelectric, Magnetic and Dielectric Properties of SrCo0.2Zn0.2Fe11.6O18.8 Hexaferrite Obtained by “One-Pot” Green Sol-Gel Synthesis Utilizing Citrus reticulata Peel Extract - Maria Vesna Nikolic; Souad Ammar-Merah; Nikola Ilić; Charanjeet Singh; Milena P. Dojcinovic; Rajshree B. Jotania (Crystals, 2023)
SrCo0.2Zn0.2Fe11.6O18.8 hexaferrite was obtained by a “one-pot” green sol-gel synthesis method utilizing aqueous mandarin orange (Citrus reticulata) peel extract as an eco-friendly reactant. The research objective was to analyze the influence of cobalt and zinc co-doping and the synthesis process on the structure, morphology, magnetic, dielectric and ferroelectric properties of strontium hexaferrite in view of future applications. Structural and morphological characterization using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy coupled to energy dispersive X-ray spectrometry (SEM-EDX) confirmed the formation of a Co and Zn ion incorporated M-type magnetoplumbite with c/a lattice parameter ratio of 3.919 as crystallite nanoplatelets of 32 and 53 nm in thickness and width, respectively. The magnetic hysteresis loop of the synthesized powder recorded by a vibrating sample magnetometer (VSM) at room temperature confirmed its ferromagnetic nature with a coercive field (Hc) of 2539 Oe and a saturation magnetization (Ms) and remanent magnetization (Mr) of 44.6 emu/g and 21.4 emu/g, respectively. Room temperature ferroelectric loops measured at 100 Hz showed a maximal (Pmax) and a remanent (Pr) polarization of 195.4 and 31.0 nC/cm2, respectively. Both increased when the magnitude of the applied electrical field increased in the 1–24 kV/cm range. The dielectric constant decreased with the frequency increase, in accordance with the Maxwell–Wagner model, while the conductivity changed according to the Jonscher power law. The complex impedance was modeled with an equivalent circuit, enabling identification of the dominant contribution of grain boundary resistance (272.3 MΩ) and capacitance (7.16 pF).